Trisomy and tetrasomy 15q11-q13 diagnosed by molecular cytogenetic analysis in two patients with mental retardation - Bouhjar, Inesse Ben Abdallah; Gmidène, Abir; Soyah, Najla; Hanene, Hannachi; Mougou, Soumaya; Elghezal, Hatem; Saad, Ali (Journal of Pediatric Genetics, 2012)
In this study, we report two patients with the supernumerary marker chromosome (15)s. The first case is an 8.5-year-old girl with an inv dup (15) syndrome, mental retardation and dysmorphic features. The second case is a 13-year-old boy with a ring chromosome 15, who was referred to the Laboratory of Cytogenetic and Biology of Reproduction in Sousse, Tunisia for mental retardation, epilepsy, speech delay, hypotonia and other mild dysmorphic features. R banding showed the presence of a marker chromosome in both cases. Molecular cytogenetic investigation using fluorescence in situ hybridization method allowed us to characterize the markers including the Prader-Willi syndrome locus that contains the small nuclear ribonucleoprotein polypeptide N (SNRPN) gene. Tetrasomy and trisomy for the 15q11-q13 chromosomal region were found in the first and the second patient, respectively. This observation reinforces the hypothesis that additional copies of proximal chromosome 15q11 segment may be causally related to mental retardation and dysmorphic features.
Keywords: Mental retardation; inv dup (15) syndrome; ring chromosome 15 syndrome; FISH